The effect of kinship on intraspecific competition in larvae of the poison frog Ameerega bassleri (Anura, Dendrobatidae) - Evan Twomey; Victor Morales; Kyle Summers (Phyllomedusa: Journal of Herpetology, 2008)
According to inclusive fitness theory, cooperation between related individuals should ameliorate the effect of intraspecific competition. However, close relatedness is also thought to increase similarity between individuals and therefore increase the risk of exploitative competition. Studies of the effects of kinship in larval amphibians have produced mixed results concerning these two hypotheses. We examined the effect of kinship on the mean and variation of mass after 30 days of growth in groups composed of either pure siblings or a mixture of five different sibships in a species of poison frog, Ameerega bassleri. We found no significant differences between sibling and mixed treatments with respect to mass or variation in mass. Our results are consistent with other studies in larval anurans which have found no differences between sibling and mixed treatments, suggesting that the effects of kin selection and genetic similarity between competitors may in some cases cancel each other out.